Clinical features and structured clinical evaluation of vasculitis - Ponte, C; Águeda, A; Luqmani, R (Elsevier, 2018)
Systemic vasculitides are a group of heterogeneous conditions with overlapping patterns of clinical and laboratory manifestations. Moreover, clinical features can be non-specific and seemingly disparate. A major factor in defining optimal therapy and measuring treatment response is careful disease assessment targeting four main domains: activity, damage, prognosis and quality of life/function. Assessment tools such as the Birmingham Activity Score and the Vasculitis Damage Index have become a core feature of clinical trials in ANCA-associated vasculitis (AAV) and formed the basis for sound clinical management of these complex conditions. We are still lacking accurate definitions of disease activity and damage progression in large-vessel vasculitis. There is an increasing interest in the role of patient-reported outcomes as a measure of disease impact; a disease-specific measure for use in AAV is being validated. We review how best to evaluate patients with large-, medium- and small-vessel vasculitis.